2017
DOI: 10.1136/sextrans-2016-053057
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of gastrointestinal infections in men who have sex with men diagnosed with rectal chlamydia infection in the UK: an ‘unlinked anonymous’ cross-sectional study

Abstract: Word count: 15642 ABSTRACT (word count 212)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 12 publications
0
20
0
Order By: Relevance
“…There are also plausible biological explanations for the overlap between Shigella and HIV epidemics, including increased shedding of Shigella species, a prolonged infectious period and increased susceptibility to Shigella in people living with HIV 16. While our data suggest that most MSM with HIV and Shigella were not clinically immunosuppressed, HIV might still affect immunological responses to Shigella , increasing the severity of clinical disease and duration of infectiousness 22…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…There are also plausible biological explanations for the overlap between Shigella and HIV epidemics, including increased shedding of Shigella species, a prolonged infectious period and increased susceptibility to Shigella in people living with HIV 16. While our data suggest that most MSM with HIV and Shigella were not clinically immunosuppressed, HIV might still affect immunological responses to Shigella , increasing the severity of clinical disease and duration of infectiousness 22…”
Section: Discussionmentioning
confidence: 70%
“…Until now, the role of sexual transmission between men in the Shigella epidemic has been largely inferred from gender ratio studies, case series and small epidemiological studies 8 9 11 16. Our study adds to this evidence base and suggests that the national increase in Shigella incidence in England might be due, at least in part, to Shigella infections in MSM with HIV.…”
Section: Discussionmentioning
confidence: 71%
“…The number and size of STEI outbreaks is likely to represent only a fraction of infections since many symptomatic individuals will not seek care or provide stool specimens for clinical diagnosis [13,61]; asymptomatic and/or persistent infections may also play a role in transmission [13,86,87] The views expressed in this publication are those of the author(s) and not necessarily those of the NHS, the National Institute for Health Research, the Department of Health or Public Health England.…”
Section: Future Implicationsmentioning
confidence: 99%
“…In addition to Shigella , a male skew for non-travel-associated enteric infections was found for Campylobacter [ 41 ]. Surveillance of MSM undergoing testing for rectal Chlamydia infections in the United Kingdom found that 1.8% of specimens contained Campylobacter spp, half of which were asymptomatic [ 42 ]. In the absence of specific treatment, asymptomatic carriage of enteric pathogens may persist for weeks after the clinical resolution of acute gastroenteritis, allowing ongoing transmission.…”
Section: Discussionmentioning
confidence: 99%